Assessing and comparing compassionate communities benefits across cities in diverse cultural contexts: a step toward the identification of the most important ones - Valentina González-Jaramillo; Alicia Krikorian; Vilma Tripodoro; Margarita Jorge; Sebastián Orellana; Francy López; Maria Clara Vélez; Tatiana Noguera; Silvina Montilla; Sibylle Felber; Sofía C. Zambrano; Steffen Eychmüller (Palliative Care and Social Practice)
Background: As Compassionate Communities (CCs) are developing worldwide, there is a growing need to systematically assess if they are having the expected effects on the community. Although having a single strategy would be ideal in terms of standardization and comparison, due to the inherent heterogeneity of CCs, it is not known how feasible this would be. Objectives: To assess the feasibility of creating a general strategy, based on the results of a series of focus groups conducted across three diverse CCs, to guide the evaluation of already existing programs and the development of new ones. Design: Focus groups in three cities, including different types of stakeholders, were conducted to identify potential outcomes (benefits) from CCs, as the base of a general strategy to assess CCs. Methods: We coded the discussions and built a list of the outcomes mentioned. Then, we merged those similar enough into a more general one that encompassed the others. We extracted from reviews all the CCs outcomes that have been measured. We merged the outcomes from the focus groups and the reviews and built a single list. Results: We obtained a final list of 46 outcomes; 44 were reported from the focus groups, and two more were added from the reviews. Of the 44 from the focus groups, 22 (50%) were present in the three CCs, 14(32%) were present in two CCs, and the remaining 8 (18%) were present only in one compassionate community. There were outcomes commonly reported both in the three CCs and in the literature reviews related to training the general community in compassion and end-of-life topics, facilitating the development of community networks, and generating public spaces for social integration. Conclusion: Half of the identified outcomes were reported in the three CCs. This indicates the feasibility of creating a single strategy but also reflects the need to leave room to include other aspects specific to each community according to its context in the assessment.